Reforming the Companies Act dispute resolution framework: a case for the establishment of a companies tribunal for Zambia - Chola, Mwewa (Department of Commercial Law, 2015)
Companies play a very important role in the economy of any country. A country's economic growth and development depend largely on whether or not its regulatory environment is conducive for enterprises to thrive. In recognition of the important role companies and businesses generally play in an economy, several developing countries have, in recent years, been carrying out reforms intended to enhance the ease of doing business in their respective countries. Zambia has been no exception. Some of the issues that are widely accepted as having an influence on the ease of doing business include the cost and length of dispute resolution for businesses. Therefore, it is unsurprising that some reforms aimed at, among other things, expediting and lowering the cost of commercial dispute resolution have taken place in Zambia. For example, the commercial list of the High Court was established in 1999with a view to expediting the resolution of commercial disputes. However, the cost of commercial dispute resolution remains of concern. The dissertation explores the Zambian Companies Act dispute resolution framework in a bid to consider its standing vis-Ã -vis enhancing Zambia's competitiveness in so far as the ease of doing business is concerned. It posits that the Companies Act resolution framework does not help Zambia's quest to enhance the ease of doing business on the dispute resolution front because it is predominantly anchored on recourse to court. A comparative study of current trends in company law dispute resolution is undertaken, which reveals a shift from reliance on the courts as the predominant dispute resolution forum to tribunal based dispute resolution. The dissertation ultimately recommends the establishment of a Companies Tribunal for Zambia as a measure that would contribute to lowering the cost of commercial dispute resolution - at least in the context of the Companies Act - and enhancing the ease of doing business in Zambia.